PRACTICAL TECHNOLOGIES OF INCREASING THE PROFESSIONAL COMPETENCE OF THE FUTURE ENGLISH TEACHER - JABBAROV, ULUGBEK (Журнал иностранных языков и лингвистики, 2024)
This article explores practical technologies aimed at enhancing the professional competence of future English teachers. It investigates innovative teaching methods, digital tools, and collaborative practices that contribute to the development of essential pedagogical and linguistic skills. The study emphasizes the role of experiential learning, continuous professional development, and the integration of technology in teacher education. By analyzing current trends and best practices, the article provides actionable insights and recommendations for teacher educators to effectively prepare future English teachers for the challenges of modern classrooms.